Procedure of Compulsory Dues Re-citing a Ship at PT Jasa Raharja (Persero) - Nanik Lestari; Kartika Wichita Aprilyani Haryaman (Pusat P2M Politeknik Negeri Batam, 2016)
This research aims to know the procedures in carrying out compulsory dues re-citing a ship using a cupon. In the discussion of the method of coupon in the procedure along with prospective partners in advance. After the deal, the service staff raharja will report the number of passengers/coupons were sold and checking stock coupons before doing the billing will be entered on the cash receipts services raharja. The result of the receipt of billing data will be inputted into DASI JR system, after that it will be verified and authorized in the form of a daily receipt of reports.